Dinamika Kekuasaan RAT di Kei: Antara Pengaruh Negara dan Kapital - Madyanto Wahyu Tryatmoko (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2010)
This paper analyses the dynamics and the changes of the authority of rats or kings in the Kei Island. This analysis compares and contrasts state and capital intervention on ethnic institutions within three periods or regimes. The comparison shows that in the colonial period, the state could not diminish the rats authority because ethnic consciousness remained strong in Kei Island. In the New Order (authoritarian) era, state and capital intervened strongly in ethnic identity through reconstructing centrally its institutional structure in order to support state-led development. Ethnic cleavages, corruptions, and abuses of rat power caused by state and capital intervention that diminish ethnicity during the New Order still remain in the Reform era. The diminishing ethnicity (ideology of ethnic group) particularly marked by a weakening of rats power contributes to the difficulties on resolving each conflict within society. However, corporatism that connected powers among state, capital, and elite (rat) cannot be well established in the Reform era because the larger civil society always controls the behaviors of ethnic groups.Keyword: Kei, power, capital, ethnic institution